The hypoxia-driven crosstalk between tumor and tumor-associated macrophages: mechanisms and clinical treatment strategies - Bai, Ruixue; Li, Yunong; Jian, Lingyan; Yang, Yuehui; Zhao, Lin; Wei, Minjie (Molecular cancer, 2022)
Given that hypoxia is a persistent physiological feature of many different solid tumors and a key driver for cancer malignancy, it is thought to be a major target in cancer treatment recently. Tumor-associated macrophages (TAMs) are the most abundant immune cells in the tumor microenvironment (TME), which have a large impact on tumor development and immunotherapy. TAMs massively accumulate within hypoxic tumor regions. TAMs and hypoxia represent a deadly combination because hypoxia has been suggested to induce a pro-tumorigenic macrophage phenotype. Hypoxia not only directly affects macrophage polarization, but it also has an indirect effect by altering the communication between tumor cells and macrophages. For example, hypoxia can influence the expression of chemokines and exosomes, both of which have profound impacts on the recipient cells. Recently, it has been demonstrated that the intricate interaction between cancer cells and TAMs in the hypoxic TME is relevant to poor prognosis and increased tumor malignancy. However, there are no comprehensive literature reviews on the molecular mechanisms underlying the hypoxia-mediated communication between tumor cells and TAMs. Therefore, this review has the aim to collect all recently available data on this topic and provide insights for developing novel therapeutic strategies for reducing the effects of hypoxia.